2016
DOI: 10.1161/jaha.116.003811
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic Performance of Treadmill Exercise Cardiac Magnetic Resonance: The Prospective, Multicenter Exercise CMR's Accuracy for Cardiovascular Stress Testing (EXACT) Trial

Abstract: Background--Stress cardiac magnetic resonance (CMR) has typically involved pharmacologic agents. Treadmill CMR has shown utility in single-center studies but has not undergone multicenter evaluation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
51
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 47 publications
(51 citation statements)
references
References 32 publications
0
51
0
Order By: Relevance
“…Varying transfer times have been achieved in treadmill Ex-CMR studies (Table 2) [27,31,33,34,[42][43][44][45]. Since progression to a CMR compatible treadmill adjacent to the scanner, all studies demonstrate scan initiation in under 30 s, as shown in Video 1 (with the exception of La Fountain et al in which removal of the face mask assessing oxygen uptake prolonged transfer time [44]) and cine imaging completion in under 60 s [42,43,45]. [45].…”
Section: Treadmill Exercise Cmrmentioning
confidence: 99%
See 1 more Smart Citation
“…Varying transfer times have been achieved in treadmill Ex-CMR studies (Table 2) [27,31,33,34,[42][43][44][45]. Since progression to a CMR compatible treadmill adjacent to the scanner, all studies demonstrate scan initiation in under 30 s, as shown in Video 1 (with the exception of La Fountain et al in which removal of the face mask assessing oxygen uptake prolonged transfer time [44]) and cine imaging completion in under 60 s [42,43,45]. [45].…”
Section: Treadmill Exercise Cmrmentioning
confidence: 99%
“…Since progression to a CMR compatible treadmill adjacent to the scanner, all studies demonstrate scan initiation in under 30 s, as shown in Video 1 (with the exception of La Fountain et al in which removal of the face mask assessing oxygen uptake prolonged transfer time [44]) and cine imaging completion in under 60 s [42,43,45]. [45]. This protocol is compared with adenosine/dobutamine pharmacological stress CMR imaging in Fig.…”
Section: Treadmill Exercise Cmrmentioning
confidence: 99%
“…The exercise stress using MRI compatible treadmill testing is another newer development in the field of stress CMR. The EXACT trial showed excellent diagnostic value and agreement with invasive coronary angiography [61]. The setup, however, poses many technical challenges and is currently limited to a few research centers.…”
Section: Cardiac Magnetic Resonance Imagingmentioning
confidence: 99%
“…The multicenter EXACT trial presented in this issue10 adds to this information. Raman et al examined 94 patients with a sophisticated dual‐imaging exercise stress protocol.…”
Section: Introductionmentioning
confidence: 97%